The upshot of Polyphenolic compounds on immunity amid COVID-19 pandemic and other emerging communicable diseases: An appraisal - Tazeddinova, D.; Khalil, A. (My University, 2020)
Polyphenols are a large family of more than 10,000 naturally occurring compounds, which exert countless pharmacological, biological and physiological benefits for human health including several chronic diseases such as cancer, diabetes, cardiovascular, and neurological diseases. Their role in traditional medicine, such as the use of a wide range of remedial herbs (thyme, oregano, rosemary, sage, mint, basil), has been well and long known for treating common respiratory problems and cold infections. This review reports on the most highlighted polyphenolic compounds present in up to date literature and their specific antiviral perceptive properties that might enhance the body immunity facing COVID-19, and other viral infectious diseases. In fact, several studies and clinical trials increasingly proved the role of polyphenols in controlling numerous human pathogens including SARS and MERS, which are quite similar to COVID-19 through the enhancement of host immune response against viral infections by different biological mechanisms. Thus, polyphenols ought to be considered as a potential and valuable source for designing new drugs that could be used effectively in the combat against COVID-19 and other rigorous diseases. Полифенолы - это большое семейство из более чем 10 000 соединений природного происхождения, которые оказывают бесчисленное количество фармакологических, биологических и физиологических преимуществ для здоровья человека, включая несколько хронических заболеваний, таких как рак, диабет, сердечно-сосудистые и неврологические заболевания. Их роль в традиционной медицине, такая как использование широкого спектра лечебных трав (тимьян, орегано, розмарин, шалфей, мята, базилик), давно и хорошо известна для лечения распространенных респираторных заболеваний и простудных инфекций. В этом обзоре рассказывается о наиболее освещенных полифенольных соединениях, представленных в современной литературе, и об их специфических противовирусных перцептивных свойствах, которые могут повысить иммунитет организма к COVID-19 и другим вирусным инфекционным заболеваниям. Фактически, несколько исследований и клинических испытаний все больше и больше доказывают роль полифенолов в борьбе с многочисленными патогенами человека, включая SARS и MERS, которые очень похожи на COVID-19 за счет усиления иммунного ответа хозяина против вирусных инфекций с помощью различных биологических механизмов. Таким образом, полифенолы следует рассматривать как потенциальный и ценный источник для разработки новых лекарств, которые можно было бы эффективно использовать в борьбе с COVID-19 и другими серьезными заболеваниями.
NATURAL PRODUCTS AND BIOPROSPECTING. - 2020.
Keywords: скопус; томсон; кларивате аналитикс; импакт-фактор 2020; зарубежное издание; дальнее зарубежье; научный журнал; периодическое издание; полифенол; covid-19; лечебные травы; респираторные заболевания; фармакология